DOI: 10.1002/9780470291313.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Thin Plates by the Double-Torsion Test Method

Abstract: Double torsion testing can produce fracture toughness values without crack length measurement that are comparable to those measured via standardized techniques such as the chevron-notch, surface-crack-in-flexure and precracked beam if the appropriate geometry is employed, and the material does not exhibit increasing crack growth resistance. Results to date indicate that 8 < W/d < 80 and L/W > 2 are required if crack length is not considered in stress intensity calculations. At L/W = 2, the normalized crack len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The double‐torsion testing technique, 3–6 which has been critically reviewed by the authors, 6 was successfully applied to determine the fracture toughness and slow crack growth behavior of porous cordierite under ambient conditions. Recent work has demonstrated that the fracture toughness values calculated by the double‐torsion test technique are equivalent to those obtained byASTM‐standardized techniques for materials with a flat R ‐curve 7 . Other researchers have proposed techniques for determining the R ‐curve using double‐torsion testing geometry 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The double‐torsion testing technique, 3–6 which has been critically reviewed by the authors, 6 was successfully applied to determine the fracture toughness and slow crack growth behavior of porous cordierite under ambient conditions. Recent work has demonstrated that the fracture toughness values calculated by the double‐torsion test technique are equivalent to those obtained byASTM‐standardized techniques for materials with a flat R ‐curve 7 . Other researchers have proposed techniques for determining the R ‐curve using double‐torsion testing geometry 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that the fracture toughness values calculated by the double-torsion test technique are equivalent to those obtained byASTM-standardized techniques for materials with a flat R-curve. 7 Other researchers have proposed techniques for determining the R-curve using doubletorsion testing geometry. 8 The double-torsion methodology was selected for testing specimens fabricated from the walls of the filter for several reasons, namely (a) the rectangular specimen geometry of double-torsion specimens can be fabricated from the walls of the filter, (b) crack length measurement by optical techniques is difficult in porous cordierite because of the large number of pores, nonreflective nature of the surface, and small crack-opening displacements, and (c) specimen-gripping is difficult for fragile porous cordierite specimens and the doubletorsion loading geometry does not require gripping.…”
Section: Introductionmentioning
confidence: 99%
“…The double-torsion test 30 was performed to determine the fracture toughness (K IC ) of the as-sintered and reduced samples at room temperature. Figure 2 provides a schematic view of the test setup and the loading configuration.…”
Section: Methodsmentioning
confidence: 99%
“…A summary of the properties relevant to this investigation is given in Table 1; density was obtained using the water displacement method in accordance with BS EN 993-1; Poisson's ratio and Young's Modulus were obtained from data sheets from the manufacturers [14][15][16]; and fracture toughness was obtained from literature for Sintox FA [17], Hexoloy SA [18], and B 4 C [19]. Ballistic performance and cost estimates were provided courtesy of Morgan Advanced Materials.…”
Section: Methodsmentioning
confidence: 99%